Femtosecond laser writing of integrated photonic circuits in diamond - Coccia Giulio; Giakoumaki Argyro N.; Bharadwaj Vibhav; Jedrkiewicz Ottavia; Ramponi Roberta; Eaton Shane M. (EPJ Web of Conferences, 2021)
Integrated photonic circuits pave the way for next generation technologies for quantum information and sensing applications. Femtosecond laser writing has emerged as a valuable technique for fabricating such devices when combined with diamond’s properties and its nitrogen vacancy color center. Such color centers are fundamental for sensing applications, being possible to excite them and read them out optically through the fabrication of optical waveguides in the bulk of diamond. We show how to integrate these building blocks in diamond, to develop proof-of-concept devices with unprecedented electric and magnetic field sensitivities.